2012
DOI: 10.3174/ajnr.a3352
|View full text |Cite
|
Sign up to set email alerts
|

Multimodal MR Imaging (Diffusion, Perfusion, and Spectroscopy): Is It Possible to Distinguish Oligodendroglial Tumor Grade and 1p/19q Codeletion in the Pretherapeutic Diagnosis?

Abstract: BACKGROUND AND PURPOSE:Pretherapeutic determination of tumor grade and genotype in grade II and III oligodendroglial tumors is clinically important but is still challenging. Tumor grade and 1p/19q status are currently the 2 most important factors in therapeutic decision making for patients with these tumors. Histopathology and cMRI studies are still limited in some cases. In the present study, we were interested in determining whether the combination of PWI, DWI, and MR spectroscopy could help distinguish olig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
79
1
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 103 publications
(99 citation statements)
references
References 28 publications
9
79
1
1
Order By: Relevance
“…Consistent with previous studies, we observed significant differences in diffusion MR measurements between 1p/19q co-deleted tumors from non-1p/19q co-deleted tumors [22][23][24][25] and IDH1 mutant from IDH1 wild-type diffuse gliomas [26]. Our findings did not appear to corroborate those of Tan et al [26], who reported a significantly higher rCBV in IDH WT compared with IDH MUT gliomas, though differences may stem from our smaller sample size as well as our more conservative statistical methods.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Consistent with previous studies, we observed significant differences in diffusion MR measurements between 1p/19q co-deleted tumors from non-1p/19q co-deleted tumors [22][23][24][25] and IDH1 mutant from IDH1 wild-type diffuse gliomas [26]. Our findings did not appear to corroborate those of Tan et al [26], who reported a significantly higher rCBV in IDH WT compared with IDH MUT gliomas, though differences may stem from our smaller sample size as well as our more conservative statistical methods.…”
Section: Discussionsupporting
confidence: 92%
“…Similarly, Lev et al [21] observed a higher maximum rCBV in oligodendrogliomas compared with astrocytomas in a similar sized cohort of patients (N = 30; 8 oligodendrogliomas; 4 WHO II and 4 WHO III) even after leakage correction; however, the relatively low number of patients and use of maximum rCBV measurements likely biased their results toward more corticallybased lesions or tumors near vascular structures. Lastly, our current results demonstrated no difference in median ADC between histologic subtypes, which corroborate the findings by Fellah et al [22], but are inconsistent with the findings from Bian et al [34], who found a lower ADC in oligodendrogliomas compared with astrocytomas. Some of the differences may have stemmed from our smaller sample size in grade II gliomas and the differences in criteria used for distinguishing oligoastrocytomas from oligodendrogliomas and astrocytomas.…”
Section: Discussioncontrasting
confidence: 51%
See 1 more Smart Citation
“…These results conflicted with those of a previous study based on CASL-derived CBF max . 12 However, a recent study by Fellah et al, 28 based on DSC-derived relative CBF, reported a result similar to that in our study. Several previous studies have also shown a significantly higher relative CBV in anaplastic oligodendrogliomas than in oligodendrogliomas, [28][29][30][31] while some other studies have reported a conflicting result.…”
Section: Discussionsupporting
confidence: 91%
“…[23][24][25] Provided that these techniques, particularly spectroscopy, continue to advance at their present rate, radiographic identification of 1p/19q status could be all that is necessary to categorize WHO grade II and III infiltrating gliomas by imaging. 18,[26][27][28][29] Our finding of an association between lower ADC values with 1p/19q codeletion has previously been described in small studies. 16,30 Further investigation will be necessary to define the optimal way of measuring ADC and to determine the physiologic correlate of ADC values in genetically defined oligodendroglioma.…”
Section: Discussionsupporting
confidence: 80%